Potential uses of web 2.0 tools for library client communication and relationship development - Lasić-Lazić, Jadranka (Array, 2009)
In this paper, the potential uses of Web 2.0 technologies for the improvement of communication with library clients are examined. Wikis, blogs, RSS, mash-ups and other Web 2.0 tools and services can assist librarians in their efforts to present information online and better connect with their clients, especially the younger generations of Internet users. In three different studies we investigated (1) the familiarity of informatics students with Web 2.0 tools, (2) the computer literacy and Internet use by librarians in higher-education institutions, as well as their assessment of the potential uses of various Web 2.0 tools for interaction with the clients of their library, and (3) the use of Web 2.0 tools on the websites of public libraries in Croatia.